LEGAL PROVERBS AND EXPRESSION IN KAILINESSE: Peribahasa Hukum dan Ekspresi dalam Bahasa Kaili - Garryn Christian Ranuntu (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This article explores legal proverbs and expressions in the Kailinesse, a regional language spoken by communities in Central Sulawesi, Indonesia. The study aims to identify and analyze the meaning and social function of proverbs related to law and social norms in Kaili culture. Using an ethnolinguistic approach, the article examines how legal proverbs reflect the cultural values, ethics, and worldview of the Kaili people, as well as their role in maintaining social order. The analysis reveals that legal proverbs in the Kailinesse not only serve as advice or warnings but also as expressions of local wisdom that encompass principles of justice, harmony, and adherence to customary rules. The findings provide insights into how the Kaili community expresses concepts of law and justice through their language and highlight the importance of proverbs as a tool for preserving cultural identity.